Does Tax Knowledge Motivate Tax Compliance in Malaysia? - Salawati, Sahari; Nivakan, Sritharan; Cheuk, Sharon Choy Sheung; Ahmad Syubaili, Mohamed (Sciedu Press, 2021)
This study aims to clarify whether tax knowledge of individual taxpayers motivates tax compliance in Malaysia. Studies with similar topics express the fact that there still exists a gap in profiling the demographic characteristics of knowledgeable taxpayers and better compliant taxpayers in Malaysia. Age, gender, income groups, and education level were the demographic variables used to study the association. The study applied a survey method for data collection. The population targeted was the individual taxpayers across Malaysia, whereby a sample of 419 respondents involved in this study. T-test, One-Way ANOVA, and Pearson correlation analysis had been employed to analyse the data. The outcome of the study reveals that knowledgeable taxpayers are not better tax complaining of taxpayers in Malaysia. Further, the relationship between tax knowledge and tax compliance is negative and insignificant. This paper studied the association of tax knowledge with tax compliance level, which attempt to contribute to the literature and aids tax administration to intensify not only tax law educations but also tax penalties for tax evaders.